CHARACTERISTICS OF CONSUMTIVE BEHAVIOR IN ONLINE SHOP: SHOPPING TRENDS DURING THE COVID-19 PANDEMIC - Usman Effendi; Rani Rahmayanti; Ryandi Ferdiannur Usman; Abubakar; Mariati MR (Kodepena Indonesia, 2021)
The aim of the research to find out whether there is a relationship between conformity and consumptive behavior of Muslim fashion products on online shop hijup consumers during the covid-19 pandemic?, to find out Is there a relationship between celebrity support and consumptive behavior in Muslim fashion products for online shop hijup consumers during the COVID-19 pandemic?, and to find out is there a relationship between conformity and celebrity support with the consumptive behavior of Muslim fashion products in online shop hijup consumers during the covid-19 pandemic?. . The research focuses on the relationship between conformity and celebrity support with the consumptive behavior of Muslim fashion products that are marketed online. The population of this research is online shop consumers who have purchased muslim fashion products at online shops and the sampling technique uses incidental sampling. The data collection method used a questionnaire with a Likert scale model given to online shop consumers. Data analysis used multiple regression stepwise method using bivariate and multivariate method. The results of the analysis found that there is a relationship between conformity and celebrity support with consumptive behavior in online consumer muslim fashion products with a contribution of 67%. Thus the results of this research can state that the higher the conformity and support of celebrities, the higher the consumptive behavior of online shop consumers and vice versa